(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
The upsurge of social media has permitted one and all to share their purchase and consuming experiences, including the usage of travel products. The study’s objective is to observe if a user’s attitude toward UGC and UGC impacts their purchase intention for a travel product. Questionnaires were distributed online to 233 people over 18 who had seen at least one travel product review. The data were analyzed using factor analysis and regressions. The data show that attitudes and perceived credibility impact purchase intentions, but user activities do not only influence purchase intentions for travel products. UGC often contains information and suggestions, and strategies for using travel products. Findings from this study are projected to extend the literature on UGC and give assistances to marketers and online tour operators.